Pharmacological activity of amino acids and prospects for the creation of drugs based on them - Davidova, Irina; Ruban, Olena; Herbina, Nataliia (Annals of Mechnikov’s Institute, 2022)
Introduction. Amino acids play an extremely important role in human life, as they are responsible for the normal functioning of the entire body. For full functioning, the human body uses 22 amino acids, 10 of which it synthesizes by itself, other 9 amino acids must be obtained from the outside. In the diet, it is necessary that all amino acids are presented in certain optimal ratios. Both a deficiency and an excess of one or another amino acid in the diet can lead to an imbalance, that is, to a violation of the balance of amino acids. Therefore, in cases of insufficient protein nutrition, it is advisable to enrich daily rations with essential amino acids in the form of various medicines based on them in order to prevent the negative impact of amino acids imbalance and for the normal functioning of all systems and organs. Therefore, the aim of this study was to summarize modern literary sources on the pharmacological action of essential amino acids, to analyze the existing drugs based on them on the pharmaceutical market of Ukraine, to substantiate the prospects and feasibility of their further inclusion in the composition of drugs for the prevention and treatment of pathologies of various systems and organs. Material & methods. The methods of marketing analysis, comparison and generalization of information were applied. The following sources were used as information materials on medicinal products: the directory of pharmaceuticals "Compendium on-line" and the State Register of Medicinal Products of Ukraine. Results & discussion. Based on the results of the analysis, it was established that the majority of medicinal products on the pharmaceutical market of Ukraine are manufactured by domestic pharmaceutical enterprises. A smaller share of medicines is imported from other countries of the world. The analysis of medicinal products by composition showed that the majority of drugs are monopreparations. According to the results of the analysis, in most cases, drugs based on amino acids are presented in the form of infusion drugs, a smaller share is allocated to solid dosage forms. Conclusion. The analysis of the pharmaceutical market of drugs based on amino acids showed that, in general, infusion drugs prevail, which are usually prescribed to patients with acute deficiency of amino acids. However, today’s realities indicate the impossibility of a balanced diet for most categories of people, which indicates the need to use drugs based on amino acids in more convenient dosage forms. it is advisable to develop new domestic medicines in solid dosage forms based on them for the prevention and treatment of pathologies of various systems and organs, which will ensure ease of use and help eliminate the deficiency of amino acids in the body. Solid dosage forms are convenient, do not require special conditions for use, and often ensure the beginning of the process of absorption by the mucous membrane of the oral cavity. All this is the reason for the prospect of expanding this segment of the pharmaceutical market. Keywords: amino acids, market analysis, solid dosage forms, research.